Cost-effectiveness of a national enterovirus 71 vaccination program in China. - Wenjun Wang; Jianwen Song; Jingjing Wang; Yaping Li; Huiling Deng; Mei Li; Ning Gao; Song Zhai; Shuangsuo Dang; Xin Zhang; Xiaoli Jia (Public Library of Science (PLoS), 2017)
Enterovirus 71 (EV71) has caused great morbidity, mortality, and use of health service in children younger than five years in China. Vaccines against EV71 have been proved effective and safe by recent phase 3 trials and are now available in China. The purpose of this study was to evaluate the health impact and cost-effectiveness of a national EV71 vaccination program in China.Using Microsoft Excel, a decision model was built to calculate the net clinical and economic outcomes of EV71 vaccination compared with no EV71 vaccination in a birth cohort of 1,000,000 Chinese children followed for five years. Model parameters came from published epidemiology, clinical and cost data.In the base-case, vaccination would annually avert 37,872 cases of hand, foot and mouth disease (HFMD), 2,629 herpangina cases, 72,900 outpatient visits, 6,363 admissions to hospital, 29 deaths, and 945 disability adjusted life years. The break-even price of the vaccine was $5.2/dose. When the price was less than $8.3 or $14.6/dose, the vaccination program would be highly cost-effective or cost-effective, respectively (incremental cost-effectiveness ratio less than or between one to three times China GDP per capita, respectively). In one-way sensitivity analyses, the HFMD incidence was the only influential parameter at the price of $5/dose.Within the price range of current routine vaccines paid by the government, a national EV71 vaccination program would be cost-saving or highly cost-effective to prevent EV71 related morbidity, mortality, and use of health service among children younger than five years in China. Policy makers should consider including EV71 vaccination as part of China's routine childhood immunization schedule.